Sugars Electrooxidation at Glassy Carbon Electrode Decorate with Multi-Walled Carbon Nanotubes with Nickel Oxy-Hydroxide - Sa, Acelino Cardoso de [UNESP]; Paim, Leonardo Lataro [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Esg, 2014)
The glassy carbon electrode modified with carbon nanotubes decorated with nickel oxy-hydroxide (GC/MWCNT/NiOOH) was used to studied electro-oxidation of glucose, galactose, xylose, arabinose and mannose in alkaline medium. Kinetic parameters such as, charge-transfer coefficient, electrocatalytic rate constant and diffusion coefficient were determined for sugars. Galactose exhibited a higher charge-transfer coefficient (0.37) with a diffusion coefficient of 1.3x10(-6) cm(2) s(-1) and showed the higher electrocatalytic rate constant of 2.1x10(4) L mol(-1) s(-1). The modified electrode exhibited a linear response to sugars concentration in the range around of 2.5x10(-4) mol L-1 to 5.6x10(-3) mol L-1 and limits of detection around of 1.9x10(-4) mol L-1 -4.3x10(-4) mol L-1.
Keywords: Electrocatalytic rate constant of sugars; Kinetic parameters; Nickel oxy-hydroxide; Carbon nanotubes; Chemically modified electrodes